Validity of a 5-minute focused echocardiography with A-F mnemonic performed by non-echocardiographers in the management of patients with acute chest pain - Sobczyk, Dorota (Cardiovasc Ultrasound, 2015)
STUDY OBJECTIVE: To validate the practicality of focused echocardiography with A-F mnemonic performed by non-specialists in patients with suspected acute coronary syndrome (ACS). DESIGN: This prospective observational study was conducted in the Emergency Room within 12 months period. Study population consisted of consecutive patients with preliminary diagnosis of an ACS. The following data were analyzed: demographics, clinical condition, medical history, ECG, transthoracic echocardiography (TTE) and levels of cardiac necrotic markers. TTE was performed within the first 15 minutes after the admission by the resident on-call. TTE images were interpreted and reported with mnemonic A-F. All studies were recorded and reviewed within 24 hours by the cardiologist. RESULTS: 1312 consecutive patients were enrolled to the study. TTE with A-F mnemonic revealed: RWMAs in 82,87% patients with confirmed ACS, other significant cardiac pathologies were found in 2,21% in ACS and 46,52% in non-ACS groups respectively. On the basis of these findings, 20 (1,92%) ACS and 29 (10,62%) non-ACS group patients underwent target operative treatment. Survey showed that both echocardiographic image acquisition and its interpretation with A-F mnemonic, took less than 5 minutes in 95% of cases. Residents found A-F mnemonic algorithm simple and useful. No differences were found in key findings between TTE performed by resident and the cardiologist. CONCLUSION: Focused echocardiography with A-F mnemonic allows both confirmation of acute myocardial ischemia and detection of the other life-threatening cardiac conditions resulting in proper bedside decision of directed treatment. Mnemonic based TTE enables reliable examination by properly trained residents.